Drug Abuse a Global Concern: Nigeria Community Survey a Logistic Regression Approach - Adubisi, O. D.; Muhammad, S. Y. (Asian Journal of Science, Technology, Engineering, and Art, 2024)
Statistics from Nigeria has shown that the prevalence rate of drug abuse/drug addiction is at the highest peak in various communities. Reports from different studies have proven the damaging effect of drugs when abused on both individuals and the general society at large. Fewer research studies have explored the association between individual characteristics and abuse of drugs especially in rural areas in Nigeria. Therefore, this research study aims to explore the association between individual characteristics and drug abuse using primary data obtained through a survey questionnaire. The binary logistic regression and chi-square statistics were used to scrutinize and determine the extent of the relationship between variables, respectively. The study results showed that most of the drug addicts were male individuals with high school (SSCE) educational qualifications. Also, the employment status of individuals was found to be significantly associated with abuse of drugs (OR = 2.23, CI: 1.24 – 4.00) while age and gender were not significantly associated with abuse of drugs, respectively. The study concludes that unemployment or non-engagement of individuals in any meaningful business/work can lead to the abuse of drugs in the town.